2013
DOI: 10.1589/jpts.25.1445
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Depression among Elderly Patients in Geriatric Hospitals

Abstract: [Purpose] The purpose of this study was to investigate the prevalence of depression among elderly patients and identify the factors influencing depression in a geriatric hospital in Korea. [Subjects] A self-report questionnaire was administered to the patients in community geriatric hospitals. Participants were 195 elderly patients. [Methods] The instruments utilized in this study were the Geriatric Depression Scale Short Form Korea (GDSSF-K), an activity of daily living scale, a self-esteem scale, a social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
1
14
0
6
Order By: Relevance
“…In this study, physical health status was found to be the most important factor associated with depression among elderly people from both communities and hospitals, and the findings were similar to the results of existing literatures (Alexopoulos, 2005;Djernes, 2006;Cole and Dendukuri, 2003;Jee and Lee, 2013). Daily exercise and sleep quality were also associated with depression among both populations, and these two variables might be indexes of physical health.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, physical health status was found to be the most important factor associated with depression among elderly people from both communities and hospitals, and the findings were similar to the results of existing literatures (Alexopoulos, 2005;Djernes, 2006;Cole and Dendukuri, 2003;Jee and Lee, 2013). Daily exercise and sleep quality were also associated with depression among both populations, and these two variables might be indexes of physical health.…”
Section: Discussionsupporting
confidence: 89%
“…Entre os preditores de associação à depressão, verificou-se que o escore QVG<60 foi a variável independente com maior poder de explicação do desfecho; os idosos com escore QVG<60 reveleram 8,6 vezes mais chances de ter depressão, em comparação aos escores mais elevados. Outros estudos também evidenciaram correlação inversa entre depressão e QV, assim como, autopercepção da saúde, atuando como fatores de vulnerabilidade para baixos escores na QV de idosos [12][13][14] .…”
Section: Discussionunclassified
“…A associação encontrada entre sexo feminino e sintomas depressivos também foi evidenciada, implicando um risco de 3,2 vezes maior em relação ao sexo masculino, consistente com outros achados 6,14,37 . Uma possível explicação para maiores escores de depressão em idosas pode ser atribuída à maior chance de admitir e queixar-se de sentimentos depressivos do que os homens idosos, que habitualmente escondem mais seus sentimentos.…”
Section: Discussionunclassified
See 2 more Smart Citations